Listening to Children: Child Consultation as a Mechanism for Participation for Girls and Boys in the School Context - Ochoa-Cervantes, Azucena (2021)
Background. The participation of girls and boys is the means through which they can exercise their citizenship; however, as various studies have shown, in the school context there are opportunities for students to have their opinion heard and taken into account, that is, for their authentic participation. Objective. To identify the concerns of girls and boys within the school context and their community and, at the same time, to analyze the possibilities of implementing child consultation in the school context. Method. A descriptive exploratory study was designed. As a means of childhood participation, 226 primary and 267 high school students participated, all from public schools located in the municipality of Querétaro. The instruments to collect the information were a consultation questionnaire and focus groups differentiated by grades. Results. The results found that students have concerns about the interpersonal relationships that occur within their school and their community; they also refer to structural and institutional aspects. Discussion. The analysis of these aspects must take into account the opinions of children to propose projects that allow the construction of environments conducive to learning, as well as to position girls, boys, and teenagers as social actors.